Planning of the Web-based E-Raport Assessment System - Febriyanto, Erick; Naufal, Romzi Syauqi; Sulistiawati, Sulistiawati (Pandawan, 2020)
In the world of information technology has changed the lifestyle in the aspect of our lives especially in the educational world. E-Raport is an academic information system used to input web-based student value data. The current value data input system is a benchmark for the creation of quality output and able to compete with other schools. One of the benchmarks that can be the competitiveness for other schools is the result of student learning assessments that are handled by each class. Problems that occur in the input of the value of Raport at SDN Sukanagara is currently still a manual that is the value of Raport recorded in the book Raport, so it takes a long time and a lot of energy needed. Research has the purpose of designing a value information system that facilitates the checking, recording and reporting of the computerized value of the students. Computerized Raport value reports can minimize errors in student data processing. This WEB based online raport is very easy data information and can be accessed anytime and anywhere, the system design works to insert and save value Report data and attendance and display info from school. The system uses data collection methods such as interviews, library studies, and system design, which are context diagrams, and prototypes. The information system of online Raport SDN Sukanagara is expected to be able to bring positive impact to the educational world, especially for SDN Sukanagara in the development of information technology applied in the world of education.